(untitled) (Research, Society and Development, 2021)
In the city of São Luís do Maranhão there was a population growth of 17% during the years 2000 to 2010. The urban growth resulting from populational growth affects the vegetation cover, in some areas this change may be positive due to the increase in vegetation or negative due to the loss of vegetation. Since the urban expansion directly affects the vegetated areas, it is interesting to carry out a constant mapping of the vegetation cover. Therefore, remote sensing and geoprocessing combined with a Geographic Information System (GIS) can be viable alternatives for studying the vegetative vigor of certain regions through the Normalized Difference Index (NDVI), to estimate the change in the vegetation resulting from the urban expansion between the years 2000 and 2010, in the capital of Maranhão. In this study, we identified the fifteen neighborhoods in the city that achieved the highest population growth, in addition, the neighborhoods were classified according to occupancy patterns. From satellite images from remote sensing, combined with geoprocessing techniques, it was possible to estimate the vegetated and non-vegetated areas of the fastest-growing neighborhoods in the city of São Luís-MA, in the years 2000 and 2010. Seven neighborhoods showed losses of vegetation over the period, another seven showed an increase in vegetation areas, and one neighborhood showed no variation.